Psychological Analysis of Manifestations of Nonverbal Intelligence of Senior Pre-Schoolers in the Context of Inclusive Education - Kolbasova, Khrystyna; Omelchenko, Iryna; Кobylchenko, Vadym; Huliaieva, Olena; Vovchenko, Olha (Journal of Intellectual Disability - Diagnosis and Treatment, 2023)
Inclusive preschool education ensures the full development of pre-schoolers with disabilities and promotes their social adaptation. The use of visual material is one of the effective means of stimulating cognitive activity in the process of preschool inclusion. The success of its perception and assimilation depends on the level of non-verbal intelligence. Aim: The research aims to analyze the manifestations of non-verbal intelligence in healthy senior pre-schoolers and children with disabilities. Methods: The research involved theoretical methods of systematization and generalization of academic information, as well as empirical methods of psychological diagnostics. Statistical indicators were determined through descriptive statistics and a one-factor analysis of variance. Results: The study's results showed a high level of nonverbal intelligence and creative abilities in healthy senior pre-schoolers and pre-schoolers with disabilities. The analysis didn’t reveal any statistically significant differences (р≥0.05) between the indicators of non-verbal intelligence of the studied healthy senior pre-schoolers and pre-schoolers with disabilities. Conclusions: children with disabilities have medium-high indicators of the development of non-verbal intelligence and creative abilities, which do not statistically differ from the indicators of their healthy peers. Prospects: The obtained results can contribute to developing adaptation schemes for children with disabilities in the context of inclusive education. The obtained data provide the background for expanding the teaching materials for developing non-verbal intelligence in inclusive groups.